Comparison of Waqaf Signs on the Indonesian Standard Mushaf and the Madinah Mushaf in QS. Al-Ahzab - Ali, Muh. Khumaidi (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
The purpose of this study is to compare the use of waqf signs in the Indonesian Standard Mushaf and the Medina Mushaf, both in terms of selecting the type of waqf sign and the location of the waqf sign. The aspect of selecting the type of waqf sign has implications for whether or not the recitation of the Qur'an is permissible, while the location of the waqf sign has implications for whether or not the meaning of the Qur'an is intact. This study uses a qualitative descriptive and analytical approach with a library research method to compare the use of waqf signs in the Indonesian Standard Mushaf and the Medina Mushaf in QS. Al-Ahzab. The results of the study indicate thatThe number of waqf signs used in the Indonesian Standard Mushaf and the Medina Mushaf is the same, namely 6 types of waqf signs, the difference is only in the selection of the type of waqf sign and the selection of the location of the waqf sign. In QS. Al-Ahzab, the location of the waqf that is only owned by the Indonesian Standard Mushaf while the Medina Mushaf does not mark it is found in 8 locations, conversely the location of the waqf that is only owned by the Medina Mushaf while the Indonesian Standard Mushaf does not mark it is found in 2 locations. The most basic and real comparison of the two Mushafs is that the Indonesian Standard Mushaf offers more waqf options than the Medina Mushaf, especially in QS. al-Ahzab. This in turn technically makes it easier for readers of the Qur'an in terms of breathing regulation, especially among Indonesians.